Type 1 interferon suppresses expression and glucocorticoid induction of glucocorticoid-induced leucine zipper (GILZ) - Dankers, Wendy; Northcott, Melissa; Bennett, Taylah; D’Cruz, Akshay; Sherlock, Rochelle; Gearing, Linden J.; Hertzog, Paul; Russ, Brendan; Miceli, Iolanda; Scheer, Sebastian; Fujishiro, Maki; Hayakawa, Kunihiro; et al. (Frontiers in Immunology, 2022)
Abstract SLE is a systemic multi-organ autoimmune condition associated with reduced life expectancy and quality of life. Glucocorticoids (GC) are heavily relied on for SLE treatment but are associated with detrimental metabolic effects. Type 1 interferons (IFN) are central to SLE pathogenesis and may confer GC insensitivity. Glucocorticoid-induced leucine zipper (GILZ) mediates many effects of GC relevant to SLE pathogenesis, but the effect of IFN on GC regulation of GILZ is unknown. We performed in vitro experiments using human PBMC to examine the effect of IFN on GILZ expression. JAK inhibitors tofacitinib and tosylate salt were used in vivo and in vitro respectively to investigate JAK-STAT pathway dependence of our observations. ChiP was performed to examine glucocorticoid receptor (GR) binding at the GILZ locus. Several public data sets were mined for correlating clinical data. High IFN was associated with suppressed GILZ and reduced GILZ relevant to GC exposure in a large SLE population. IFN directly reduced GILZ expression and suppressed the induction of GILZ by GC in vitro in human leukocytes. IFN actions on GILZ expression were dependent on the JAK1/Tyk2 pathway, as evidenced by loss of the inhibitory effect of IFN on GILZ in the presence of JAK inhibitors. Activation of this pathway led to reduced GR binding in key regulatory regions of the GILZ locus. IFN directly suppresses GILZ expression and GILZ upregulation by GC, indicating a potential mechanism for IFN-induced GC resistance. This work has important implications for the ongoing development of targeted GC-sparing therapeutics in SLE.